Cerium and higher plants - Kastori Rudolf R.; Maksimović Ivana V.; Putnik-Delić Marina I. (Zbornik Matice Srpske za Prirodne Nauke)
Rare earth elements (REEs) or terrae rarae (TR) are a group of 17 heavy metals which include 15 elements belonging to the lanthanide (Ln) group, as well as scandium and yttrium. REEs are very similar in chemical and physical properties. Lanthanides are considered as rare micro elements, which is not entirely true. Namely, the amount of cerium (Ce) in the Earth’s crust is slightly higher than the amount of Cu, Pb or Zn. Except for Eu (+2 and +3) and Ce (+3 and +4), REEs usually form trivalent cations. Studies of individual REEs elements are mostly focused on the effects of Ce and La. Cerium is nowadays used in agriculture, as a microfertilizer. However, it is not essential for higher plants. The effects of Ce on life processes of plants range from stimulation to inhibition, depending on its concentration (hormesis), plant species, the stage of development, method of application and ecological factors. Lower concentrations and amounts of Ce can be beneficial for nutrient uptake, seed germination, photosynthesis, growth, dry matter accumulation and for alleviating different kinds of stress in plants. Cerium decreases oxidative stress and increases antioxidative capacity of plants. Higher concentrations of Ce reduce plant growth. Excessive amounts of Ce have cytotoxic and genotoxic effects. The available literature on the influence of lower concentrations of Ce on life processes in plants suggests positive outcomes. How- ever, further fundamental investigations shall lead to better understanding of the physiological mechanisms of the impact of Ce on plant metabolisms.